DISSECTING THE CONTENTS OF LAW OF INDONESIA ON HALAL PRODUCT ASSURANCE - Hakim, Aal Lukmanul (Indonesia Law Review, 2015)
Indonesia with its majority Moslem population and even the biggest Moslem nation in the world has obligations to its citizens to assurance the halal products (halal) for consumption and/or used as a constitutional obligation to be enforceable and applicable. The constitutional obligation is granted in the form of legal certainty covering the halalness of all products either to those useable, consumed and/or utilized by the society. Upon the legalization and enactment of Law of the Republic of Indonesia Number 33 year 2014 regarding Halal Product Assurance is the evidence of constitutionally protection commitment. Having this Halal Product Assurance Law, the people may consume and/or use any products safely, pleasantly, securely and healthy, in addition to the increase of added value for Business Entities to product and sell Halal Products.